1-UFG-GO Se o polinômio x³ + kx² - 2x + 3 é divisivel pelo polinomio x2 -x + 1 então o quociente é:
2-UFSE se 2x-3/x² -6x+5 = A/x-5 + B/x-1 então:
Anexos:
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
7)
x³ + kx² - 2x + 3 | x² - x + 1
- x³ + x² - x x + (k+1)
----------------
(k+1)x² - 3x + 3
- (k+1)x² + (k+1)x - (k+1)
-----------------------------------
(k-2)x - k + 2
r(x) = (k - 2).x - k + 2
Devemos ter r(x) = 0, logo:
(k - 2).x - k + 2 = 0 => k = 2
O quociente é:
q(x) = x + (k + 1)
q(x) = x + 2 + 1
q(x) = x + 3
Letra B
8)
(2x-3)/(x²-6x+5) = A/(x-5) + B/(x-1)
(2x-3)/(x²-6x+5) = [A.(x-1)+B.(x-5)]/(x-5).(x-1)
(2x-3)/(x²-6x+5) = [A.(x-1)+B.(x-5)]/(x²-6x+5)
2x - 3 = A.(x - 1) + B.(x - 5)
2x - 3 = A.x - A + B.x - 5B
2x - 3 = (A+B).x - A - 5B
Devemos ter:
• A + B = 2
• -A - 5B = -3
Letra D
Perguntas interessantes
Biologia,
4 meses atrás
Matemática,
4 meses atrás
ENEM,
5 meses atrás
Português,
10 meses atrás
Geografia,
10 meses atrás